Atlantic‐Pacific Gradients Drive Last Millennium Hydroclimate Variability in Mesoamerica. Issue 13 (30th June 2020) - Bhattacharya, Tripti; Coats, Sloan
Abstract: The paleoclimatic record from Mexico and Central America, or Mesoamerica, documents dramatic swings in hydroclimate over the past few millennia. However, the dynamics underlying these past changes remain obscure. We use proxy indicators of hydroclimate to show that last millennium hydroclimate variability was dominated by opposite‐signed moisture anomalies in northern and southern Mesoamerica. This pattern results from changes in moisture convergence driven by Atlantic‐Pacific interbasin temperature gradients. While this pattern is reproduced by several models and multiple experiments with a single model, models appear to disagree about the underlying dynamics of this interbasin gradient. Moreover, disagreement about the interbasin gradient, and associated hydroclimate pattern, dominates spread in 21st century regional hydroclimate projections. These results emphasize the role of interbasin asymmetries in governing past and future regional climate change. They also demonstrate that paleoclimate studies can elucidate mechanisms directly relevant to projecting future hydroclimate in climate change hot spots like Mesoamerica. Plain Language Summary: Models project a drier future for Mexico and Central America in the 21st century. This region is also known to have historically experienced long‐term droughts, many of which lasted decades to centuries. Here, we use a combination of data and models to show that, over the last millennium, dry intervals in southern Mesoamerica were accompanied by wetter conditions in northern Mexico. This pattern results from changes in wind fields and moisture transport driven by fluctuations in the temperature difference between the tropical Atlantic and Pacific. However, models disagree about the processes influencing Atlantic and Pacific temperature variability over the last millennium, and these model biases are likely to have significant impacts on our ability to accurately project hydroclimate changes in this drought‐vulnerable region. These results suggest that temperature differences between the Atlantic and the Pacific play an important role in both past and future climate change in Mesoamerica. Key Points: Different proxy indicators of hydroclimate from Mesoamerica show consistent patterns of variability over the last millennium Variations in the Atlantic‐Pacific temperature gradient create opposite‐signed hydroclimate anomalies in southern and northern Mesoamerica Disagreement about future changes to the interbasin gradient changes drives model spread in Mesoamerican hydroclimate projections